La diffusion des rickshaws au Tchad, une réponse « par le bas » aux besoins de mobilité des populations urbaines ? - Ronan Mugelé; N'Dilbé Tob-Ro (EchoGéo)
In Chad, as well as in other sub-Saharan countries, the governement is struggling to implement effective transport policies that are accessible to a rapidly growing, largely poverty-stricken, and rapidly urbanizing population. To address these challenges, the private and informal sector appears as a reliable partner. After the well-known success of motorcycle cabs or "clandos," recent years have seen the rapid spread of another light means of transport, the rickshaw, which is now used in most urban centers. This article analyzes the current role of the rickshaw in the system of urban mobility in Chad. It describes the mechanisms of its spatial diffusion on a national scale, as well as the local practices and representations associated with this successful newcomer, through the case of Abéché.